2020
DOI: 10.2147/opth.s266218
|View full text |Cite
|
Sign up to set email alerts
|

<p>Demography, Risk Factors, and Clinical and Microbiological Features of Microbial Keratitis at a Tertiary Eye Hospital in Nepal</p>

Abstract: Background: Infective keratitis is the most common corneal pathology in developing countries. Updated knowledge is needed for its control and proper management. Methodology: All cases of presumed microbial keratitis that presented in an 18-month period from October 2013 to March 2015 were enrolled. Data collected were demographic profile, risk factors, clinical features, and organisms isolated and their sensitivities. Results: A total of 602 cases of microbial keratitis were enrolled. Mean age of subjects (598… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
4
11
0
Order By: Relevance
“…64 percent of the patients in our study belonged to rural background and the major predisposing factor among them was trauma by vegetative matter. 33.3% of the patients in our study were farmers The results of our study are also in concordance with study by Bajracharya L., et al [10] in which they reported nearly 64% of the patients belonged to agricultural sector and trauma was the most common predisposing factor in 38.3% patients. 30.7 percent of the patients in our study presented in the months of August and September combined.…”
Section: Number Of Patientssupporting
confidence: 92%
“…64 percent of the patients in our study belonged to rural background and the major predisposing factor among them was trauma by vegetative matter. 33.3% of the patients in our study were farmers The results of our study are also in concordance with study by Bajracharya L., et al [10] in which they reported nearly 64% of the patients belonged to agricultural sector and trauma was the most common predisposing factor in 38.3% patients. 30.7 percent of the patients in our study presented in the months of August and September combined.…”
Section: Number Of Patientssupporting
confidence: 92%
“…2 The incidence of fungal ulcer is high in hot and humid tropical climate as well as in developing countries where agriculture is the main occupation. [3][4][5][6] Hospital-based studies in these regions, including our previous descriptive study, report a higher proportion of fungi compared to bacterial. [3][4][5][6] Hence detail study of fungal keratitis is important in endemic regions for planning proper control and management of fungal keratitis.…”
Section: Introductionmentioning
confidence: 65%
“…[3][4][5][6] Hospital-based studies in these regions, including our previous descriptive study, report a higher proportion of fungi compared to bacterial. [3][4][5][6] Hence detail study of fungal keratitis is important in endemic regions for planning proper control and management of fungal keratitis.…”
Section: Introductionmentioning
confidence: 65%
“…In Nepal, it accounts for 0.54% of bacterial isolates in keratitis. 1 Most of the case series of Moraxella had shown affection of older age group with average age of 58 to 70 years with slight female preponderance. 2 - 3 , 5 - 6 In our study, the patient had been middle age healthy female.…”
Section: Discussionmentioning
confidence: 99%
“…Common causative agents are streptococcus, staphylococcus and pseudomonas species. 1 Moraxella species are rare cause of keratitis accounting for 0.3 to 5% of bacterial isolates in different countries. 2 - 3 Moraxella are gram-negative, aerobic, diplobacilli, found as commensals in oropharynx, mucous membranes and skin and can cause systemic infections.…”
Section: Introductionmentioning
confidence: 99%